2013
DOI: 10.1080/00140139.2012.752528
|View full text |Cite
|
Sign up to set email alerts
|

Low back loads while walking and carrying: comparing the load carried in one hand or in both hands

Abstract: Carrying a load in one hand (30 kg) resulted in more spine load than splitting the same load between both hands (15 kg). When carrying double the load in both hands (30 kg in each hand vs. 30 kg in one hand), spine load decreased, suggesting merit in balancing load when designing work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 16 publications
2
49
0
Order By: Relevance
“…The torque generated is not dependent only on the mass, but on the moment arm, or the distance from the pivot point to the point where the force is applied. For example, carrying a load out in front with elbows bent 90°, or in one hand at the side of the body imposes a greater compressive load on the spine than dividing the weight between two hands and carrying it at one's sides, close to the body (Box 4) [24,25]. In the thoracic spine, holding 11 lbs (5 kg) in each hand with elbows flexed to 90° has been reported to increase the compressive loads at T8 and T12, ~ 3.0 and 3.5 times that of standing, respectively [22].…”
Section: Boxmentioning
confidence: 99%
See 1 more Smart Citation
“…The torque generated is not dependent only on the mass, but on the moment arm, or the distance from the pivot point to the point where the force is applied. For example, carrying a load out in front with elbows bent 90°, or in one hand at the side of the body imposes a greater compressive load on the spine than dividing the weight between two hands and carrying it at one's sides, close to the body (Box 4) [24,25]. In the thoracic spine, holding 11 lbs (5 kg) in each hand with elbows flexed to 90° has been reported to increase the compressive loads at T8 and T12, ~ 3.0 and 3.5 times that of standing, respectively [22].…”
Section: Boxmentioning
confidence: 99%
“…Bending forward will also increase the compressive and shear loads on the spine (24). Therefore, in theory, a person with a history of spine fractures might be able to hold a given weight safely if the weight is divided between hands held at sides, but not if it is held in front of the body, or while bending forward with it.…”
Section: Boxmentioning
confidence: 99%
“…Unilateral load carriage is known to be more hazardous to the musculoskeletal system than bilateral loading (DeVita et al (1991), Fowler et al (2006 or McGill et al (2013)), leading finally to many disorders of which the most common is low back pain. We found that walking with asymmetric loads from 0 to 11.33 kg, in 2.26 kg increments, do not affect the COR, even though the two areas defined under GRF curves tend to increase with the increase in load.…”
Section: Discussionmentioning
confidence: 99%
“…Several sophisticated analytical models exist that allow estimation of the spinal load when carrying a weight (McGill and Norman 1986;Cholewicki and McGill 1994;Stokes and Gardner-Morse 1995;Granata and Marras 2000;De Zee et al 2007). McGill, Marshall, andAndersen (2013) estimated spinal loads when carrying weights in one hand and in both hands. They found that carrying a weight in one hand resulted in substantially more compressive load on the low back than when the weight was split evenly between both hands.…”
Section: Introductionmentioning
confidence: 99%